Characteristics of Neurophobia Among Medical Students: A Single-Centre Study In Indonesia - Zairinal, Ramdinal Aviesena; Hidayati, Diah Balqis Ikfi (Writing Center IMERI FMUI, 2024)
Backgrounds: Neurophobia is a fear of neurology among medical students. Early detection is necessary for prevention and further treatment because neurophobia will have a negative impact on patient care. The objective of this study is to investigate the occurrence of neurophobia among medical students. Methods and Materials: A cross-sectional study using the validated NeuroQ questionnaire was distributed to Faculty of Medicine, University of Indonesia (FMUI) students. Inclusion criteria are age ≥18 years, pre-clinical and clerkship students, able to read, understand, speak Indonesian and answer questions independently, and willing to participate in research. Exclusion criteria are questionnaire data that is not filled in completely. Descriptive and comparative tests were carried out to analyze variables. Results: A total of 89 FMUI students completed the questionnaire with an average NeuroQ score of 17.22 (SD 1.999). Most of the students (73 students; 82%) had a NeuroQ score ≥16 points, 32 students (36%) had neurophobia, and 41 students (46%) had marked neurophobia. Gender was not related to the total NeuroQ score (p=0.815). There was no significant difference between pre-clinical and clerkship students with the total NeuroQ score (p=0.246). Conclusions: Most students experience neurophobia. New strategies are needed to change students' perceptions of neurology.